Immune-profiling of SARS-CoV-2 viremic patients reveals dysregulated innate immune responses - Sun, Xiaoming; Gao, Ce; Zhao, Ke; Yang, Yanhui; Rassadkina, Yelizaveta; Fajnzylber, Jesse; Regan, James; Li, Jonathan Z.; Lichterfeld, Mathias; Yu, Xu G. (Frontiers in Immunology, 2022)
SARS-CoV-2 plasma viremia has been associated with severe disease and death in COVID-19. However, the effects on immune responses in blood cells remain unclear. The current study comprehensively examined transcriptional signatures of PBMCs involving T cells, B cells, NK cells, monocytes, myeloid dendritic cells (mDCs), and plasmacytoid dendritic cells (pDCs) respectively, from three different groups including moderate patients(nM), severe patients with (vS) or without detectable plasma viral load (nS). Whole transcriptome analysis demonstrated that all seven immune cells were clustered together with disease severity regardless of cell type. Supervised clustering analysis demonstrated that mDCs and pDCs gene signatures could distinct disease severity. Notely, the vS group enriched in DNA repair, E2F targets, and G2M checkpoints. While the nM group enriched in interferon responses. Moreover, we observed a highly impaired induction of Interferon responses accompanied by imbalanced type I interferon sensing and an excessive inflammatory response in severe patients (nS and vS). To sum, our study provides detailed insights into the systemic immune response to SARS-CoV-2 infection and reveals profound alterations in seven major immune cells in COVID-19 patients.